To use substitution, we must isolate #x# on one of the sides in one of the equations. The first equation looks simple enough to manipulate and isolate #x#.

We can add #7y# to both sides of the first equation to get:

#x = 7y + 16#

Now, we can turn towards the second equation. We can first simplify the left side by adding the #x#'s ( #-3x# and #6x#) to make the second equation:

#3x = -3#

Although we could just solve for #x# here, we should use substitution. We can know replace #x# with the equal value #7y + 16# (from the first equation) to make the second equation:

#3(7y + 16) = -3#

Now we can solve the second equation from there by distributing, subtracting, and dividing:

#21y + 48 = -3#

#21y = -51#

#y = -51/21 = -17/7#

To solve for #x#, we can substitute our value for #y# into the first equation (#x = 7y + 16#) to get:

#x = 7(-17/7) + 16#

#x = -17 + 16#

#x = -1#.

Therefore, our final solution is #x=-1# and #y = -17/7#